Pyrethroid insecticide exposure and reproductive hormone levels in healthy Japanese male subjects - Yoshinaga, J.; Imai, K.; Shiraishi, H.; Nozawa, S.; Yoshiike, M.; Mieno, M. N.; Andersson, A.‐M.; Iwamoto, T. (Andrology (Oxford), 2014)
Summary The associations between serum levels of reproductive hormones (follicle‐stimulating hormone, luteinizing hormone, testosterone, sex hormone‐binding globulin, inhibin B and calculated free testosterone) and urinary metabolite concentration of pyrethroid insecticides [3‐phenoxybenzoic acid (3‐PBA)] were explored in 322 male university students in suburban Tokyo. The subjects constituted part of a large cross‐sectional survey on the reference value of semen quality of Japanese men. Urinary 3‐PBA was detectable in 91% of the subjects demonstrating ubiquitous exposure among the general population. However, there were no associations between urinary 3‐PBA and serum hormone levels. This result was inconsistent with those reported in China and the USA for subjects who had similar levels of urinary 3‐PBA to the present subjects. One of the possible reasons of the inconsistency might be different composition of pyrethroid insecticides to which the subjects were exposed; 3‐PBA is a common metabolite of a number of pyrethroids and thus lacks specificity to compounds that may have different potentials of reproductive toxicity. Another reason might be related to the fact that our subjects were university students who were not aware of their own fertility, whereas the previous study subjects were infertility patients. However, the multiple regression models could explain only a limited fraction of total variance in serum levels of hormones. Identification of other contributors is warranted.